Ronald Reagan : fate, freedom, and the making of history - Diggins, John P. (New York : W. W. Norton & Co., 2007)
'Following his departure from office, Ronald Reagan was marginalized thanks to liberal biases that dominate the teaching of American history, says John Patrick Diggins. Yet Reagan, like Lincoln (who was also attacked for decades after his death), deserves to be regarded as one of our three or four greatest presidents. Reagan was far more active a president and far more sophisticated than we ever knew. His negotiations with Mikhail Gorbachev and his opposition to foreign interventions demonstrate that he was not a rigid hawk. And in his pursuit of Emersonian ideals in his distrust of big government, he was the most open-minded libertarian president the country has ever had; combining a reverence for America's hallowed historical traditions with an implacable faith in the limitless opportunities of the future.--From publisher description.'--From source other than the Library of Congress
Includes bibliographical references (p. [433]-464) and index
Keywords: Reagan, Ronald; Reagan, Ronald -- Political and social views; Presidents -- United States -- Biography; Conservatism -- United States -- History -- 20th century; United States -- Politics and government -- 1981-1989